Childbirth in South Sudan: Preferences, practices, and perceptions in the Kapoetas - Heather M. Buesseler; James Yugi (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2016)
Background: Focus group discussions (FGDs) were designed to better understand the community's views and preferences around maternity care to design a communications campaign to increase facility deliveries and skilled attendance at birth in the three county catchment areas of Kapoeta Civil Hospital. Methods: Twelve FGDs were conducted in Kapoeta South, Kapoeta East, and Kapoeta North counties. Four South Sudanese facilitators (two women, two men) were hired and trained to conduct sex-segregated FGDs. Each had 8-10 participants. Participants were adult women of reproductive age (18-49 years) and adult men (18+ years) married to women of reproductive age. Results: The majority of participants' most recent births took place at home, though most reportedly intended to give birth in a health facility and overwhelmingly desire a facility birth next time. Husbands and the couple's mothers are the primary decision-makers about where a woman delivers. More men than women preferred home births, and they tend to have more negative opinions than women about health facility deliveries. Though participants acknowledge that health facilities can theoretically provide better care than home births, fear of surgical interventions, lack of privacy, and perceived poor quality of care remain barriers to facility deliveries. Recommendations: Interventions encouraging facility births should target the decision-makers-husbands and a couple's mothers. Improvements in quality of care are needed in health facilities. Developing social network interventions that circulate positive experiences about delivering in health facilities may be effective in changing public perception and decision-making about facility deliveries. Additional research and pilot testing is needed to more fully inform effective social and behavioural change strategies around maternal health in the Kapoetas in South Sudan.